1998
DOI: 10.1111/j.1525-1446.1998.tb00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Home Health Nurses' Initial Experiences with Wireless, Pen‐Based Computing

Abstract: Eight home health nurses from the Visiting Nurse Service of New York participated in a focus group discussion after their initial experiences using wireless, pen-based computing in the inner-city, home care environment. Transcripts of the nurses' responses to open-ended questions were analyzed and central themes were found, following the method of concept analysis described by Strauss and Corbin (1990). The central concepts were "Readiness," "A thousand pounds on my back," "Call for support," "Problems with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…1996, Daly et al. 2002), but most studies on computerized nursing documentation have focused on nurses’ attitudes towards computers and seldom specifically explored the influence of this technology on nurses’ perceptions of the documentation process (Stronge & Brodt 1985, Harris 1990, Simpson & Kenrick 1997, Wilson & Fulmer 1998, Stricklin et al. 2003, Darbyshire 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1996, Daly et al. 2002), but most studies on computerized nursing documentation have focused on nurses’ attitudes towards computers and seldom specifically explored the influence of this technology on nurses’ perceptions of the documentation process (Stronge & Brodt 1985, Harris 1990, Simpson & Kenrick 1997, Wilson & Fulmer 1998, Stricklin et al. 2003, Darbyshire 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nurse participants wrote negative comments about device features (data entry, response time, system downtime, and concerns about theft and loss), similar to comments from previous reports. 10,11,19,20 However, the clustering of these negative items in one construct may pose a response bias for the ESPDA, which could be eliminated by changing the language or wording of some items. [34][35][36] Because user concerns about PDA features such as screen size, device theft, and data transmission are not unique to this study, these issues deserve further research and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Early qualitative studies found that although home health nurses welcomed using penbased wireless computers in their daily practice, they were concerned about issues of hardware maintenance, technical support, and device theft or loss. 19,20 Penbased computers improved the quality of documentation for home health nurses compared with manual records by providing immediate access to an easily readable record and decreasing calculation errors, but the time spent on patient care and documentation did not change significantly. 21 In addition, PDAs were used to establish a database for an intravenous resource nurse service, but its use was limited by slow response time after entering large amounts of data and by the attention needed to maintain the hardware (eg, keeping the battery charged, avoiding accidentally dropping the PDA).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Nurses' perceptions of using handheld computers have been explored for documenting home care (Wilson & Fulmer 1997, 1998 and managing intravenous consultation services (Bosma et al 2003). Although nurses valued the PDA's assistance in organizing daily practice, retrieving point-ofcare information, and integrating with statistical analysis software, these studies reported that nurses experienced obstacles such as fear of losing PDAs or styluses, data transmission problems, software (screen) freezes, hardware breakage and slow responsiveness after entering a large amount of patient data.…”
Section: Personal Usage Issuesmentioning
confidence: 99%
“…Nurses’ perceptions of using handheld computers have been explored for documenting home care (Wilson & Fulmer 1997, 1998) and managing intravenous consultation services (Bosma et al. 2003).…”
Section: Introductionmentioning
confidence: 99%